ESTUDOS TOXICOLÓGICOS DO OXICLORETO DE COBRE PARA TILÁPIA VERMELHA (OREOCHROMIS SP.) - Boock, M.v. [UNESP]; Machado, J.g. [UNESP] (Instituto Biológico, 2024)
The present study was carried out with the objective of determining the acute toxicity as well as the risk of intoxication due to environmental contamination by copper oxychloride fungicide and the copper bioconcentration for the red tilapia (Oreochromis sp.). In the test of acute toxicity, the tilapia fingerlings with approximately two months of age were exposed to growing concentrations of the fungicide copper oxychloride for 96 hours. The risks of contamination were calculated through the comparison among CL50-96 hours calculated and the Estimated Environmental Concentration (EEC) of the fungicide. In the bioconcentration test, the fishes were exposed to the concentrations of 0.0200 and 0.0769 mg/L of copper for 192 hours and after transferred to clean water for 144 hours for the observation of the capacity of purification of this metal by the fishes. The CL50 calculated was 129.21 mg/L of copper oxychloride, corresponding to 76.91mg/L of metallic copper. In the bioconcentração test the copper accumulation was observed in both tested concentrations, however the metal was only eliminated totally by the the smallest concentration (0.02 mg/L) exposed fish. The risks of contamination of the red tilápia were considered low in the conditions of this study.

O presente estudo foi conduzido com o objetivo de determinar a toxicidade aguda, o risco de intoxicação devido à contaminação ambiental pelo fungicida oxicloreto de cobre e a bioconcentração do cátion Cu +2 na tilápia vermelha (Oreochromis sp.). No teste de toxicidade aguda, os alevinos de tilápia com aproximadamente dois meses de idade foram expostos à concentrações crescentes do fungicida oxicloreto de cobre por 96 horas. Os riscos de intoxicação foram determinados através da comparação entre a CL50 -96 horas calculada e a Concentração Ambiental Estimada (CAE) do fungicida. No teste de bioconcentração, os peixes foram expostos às concentrações de 0,02 e 0,0769 mg/L do cátion cobre (Cu +2 ) por 192 horas e em seguida transferidos para água livre de cobre por 144 horas visando a observação da capacidade de depuração deste metal pelos animais. A CL50 obtida foi de 129,21 mg de oxicloreto de cobre/L, correspondendo a 76,91mg de cobre metálico/L. No teste de bioconcentração observou-se o acúmulo de cobre em ambas as concentrações testadas, porém o metal só foi totalmente eliminado pelos peixes expostos a menor concentração (0,02mg/L). Os riscos de intoxicação devido à contaminação ambiental para a tilápia vermelha foram considerados baixos nas condições estudas.
TOXICOLOGICAL STUDIES OF COPPER OXYCHLORIDE FOR THE RED TILAPIA (OREOCHROMIS SP.)
Keywords: Saint Peter’s fish; Oreochromis sp.; acute toxicity; copper oxicloride; bioconcentration.; Tilápia vermelha; Oreochromis sp.; toxicidade aguda; oxicloreto de cobre; bioconcentração; Concentração Ambiental Estimada (CAE).